Roadmap on Cervical Cancer Prevention - SANKARANARAYANAN, R (Indonesian Journal of Cancer, 2010)
CERVICAL CANCER CONTROL:1. VACCINATION2. SCREENING LINKED WITH TREATMENT3. EARLY CLINICAL DIAGNOSIS LINKED WITH TREATMENTÂ Full text : http://www.scribd.com/doc/43594755/Roadmap-on-Cervical-Cancer-Prevention